The distribution of blood cells on haemacytometer counting chambers with special reference to the amended British Standards Specification 748 (1958). Issue 3 (May 1961) - Sanders, C.; Skerry, D. W.
Abstract : The distribution of leucocytes and erythrocytes on the haemacytometer counting chamber is shown. Differences between total leucocyte counts on single and double-ruled chambers are given and the effect of different lengths of cover glass are discussed. An assessment of the relative accuracy of the amended British Standards Specification (B.S.S.) 748 (1958) double-ruled bright line chamber and the old B.S.S. chambers in made.